2017
DOI: 10.1002/clc.22694
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic evaluation of the right ventricle: Clinical implications

Abstract: Interest in evaluation of the right ventricle (RV) has increased recently. With the growth of new echocardiographic techniques and technology, there has been a corresponding increase in the ability to evaluate the RV, both qualitatively and quantitatively. Older echocardiographic techniques, such as right ventricular fractional area of change, tricuspid annular plane systolic excursion, and tissue S 0 , and newer echocardiographic techniques including 3-dimensional evaluation and global longitudinal strain, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 33 publications
0
42
1
Order By: Relevance
“…Therefore, detection of PH in PF patients by TTE can be confirmed by RHC although it may not change the clinical management given there is no approved PH-targeted therapy currently available for this patient population. TTE is also widely used to visualize right ventricular morphology and detect right ventricular dysfunction [65]. Commonly used RV indices to assess for PH by TTE include RV/LV basal diameter ratio to assess for RV dilatation, and tricuspid annular plane systolic excursion (TAPSE), fractional area change, and RV pulsed tissue doppler S wave velocity to evaluate for RV dysfunction [62].…”
Section: Transthoracic Echocardiographymentioning
confidence: 99%
“…Therefore, detection of PH in PF patients by TTE can be confirmed by RHC although it may not change the clinical management given there is no approved PH-targeted therapy currently available for this patient population. TTE is also widely used to visualize right ventricular morphology and detect right ventricular dysfunction [65]. Commonly used RV indices to assess for PH by TTE include RV/LV basal diameter ratio to assess for RV dilatation, and tricuspid annular plane systolic excursion (TAPSE), fractional area change, and RV pulsed tissue doppler S wave velocity to evaluate for RV dysfunction [62].…”
Section: Transthoracic Echocardiographymentioning
confidence: 99%
“…5 RVOT contribute 20% of RV contraction and 15% stroke volume of RV. 7,8,11,13 In our study, we correlate the other RV function parameter such as RVOT FS, TAPSE and S' with RV FAC. We found that TAPSE had high positive correlation than other (r=0.788) (P<0.001).…”
Section: Discussionmentioning
confidence: 94%
“…RV dysfunction is emerging as a novel marker for risk stratification in SCD. Although RVFAC is a standard measure for echocardiographic assessment of RV function, 20 it is not clear at this time which measure of RV function would be the most suitable for risk stratification. Previous work has identified RV dysfunction as a potential predictor of SCD risk, although it has not been shown for quantitative measures in clinically acquired echocardiograms.…”
Section: Discussionmentioning
confidence: 99%